2011
DOI: 10.1587/transcom.e94.b.618
|View full text |Cite
|
Sign up to set email alerts
|

NerveNet: A Regional Platform Network for Context-Aware Services with Sensors and Actuators

Abstract: SUMMARYWireless access networks of the future could provide a variety of context-aware services with the use of sensor information in order to solve regional social problems and improve the quality of residents' lives as a part of the regional infrastructure. NerveNet is a conceptual regional wireless access platform in which multiple service providers provide their own services with shared use of the network and sensors, enabling a range of context-aware services. The platform acts like a human nervous system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…The entire network is managed from one PC called the Network Manager (NM) [7]. An NM needs to be connected to a base station only when network configuration is necessary (when a network is created or the network topology has changed).…”
Section: Network Service Platformmentioning
confidence: 99%
See 1 more Smart Citation
“…The entire network is managed from one PC called the Network Manager (NM) [7]. An NM needs to be connected to a base station only when network configuration is necessary (when a network is created or the network topology has changed).…”
Section: Network Service Platformmentioning
confidence: 99%
“…NerveNet was originally designed and developed in 2008 as an access network for providing context-aware services with the use of sensors and actuators [2]- [7]. Since 2011, under a project led by the Ministry of Internal Affairs and Communications to strengthen information and communication networks, we have conducted R&D to upgrade NerveNet and verified its scalability and stability using a large-scale test bed of approximately 30 base stations constructed on two campuses of Tohoku University, Sendai, Japan [8].…”
Section: Introductionmentioning
confidence: 99%
“…1, SU is a mobile terminal, and collects information from sensor 1 and securely transfers it to its private CSG 1 when it is located in SN 1 . NerveNet assures secure communication among SU, CSG, and BS [8]. The SU therefore has control of the collection and storage of sensor information.…”
Section: System Descriptions and Security Requirementsmentioning
confidence: 99%
“…Core optical networks serve for global transit of data and regional networks are edge networks designed to provide services to local residents and to people visiting an area. With the regional network in the AKARI project, we are conceiving a platform network architecture called NerveNet [8], [9], [10], which accommodates diverse services involving future applications of mobile terminals and sensors. The notable feature of NerveNet is that most of its communications are performed in a local area without traversing a global transit network, since it is observed that many individual or community services are oriented to users in a region.…”
Section: Introductionmentioning
confidence: 99%
“…NWGN is the Japanese vision of developing a trustworthy future network infrastructure to provide service adaptive for future society, which is physically composed of global transit network for global transmissions and regional network [5] for local transmissions. Herein, we focus on security designs for regional network.…”
Section: Introductionmentioning
confidence: 99%